Nível de formalização na logística de suprimentos da indústria automotiva: análise do caso das montadoras - Guarnieri, Patrícia (2006)
One of the major challenges for the companies of industrial segment is to know how to manage its supply chain in an efficiently and comprehensively form. The automotive segment can be considered representative in this sense and deserves to be noticeable once it presents considerable initiatives in the supply chain management (SCM). Thus, it is prominent to study the main factors of the SCM that impacts in the supplying of Brazilian automotive industries output. In order to answer this question, it was accomplished an applied, exploratory, descriptive and qualitative research, through inductive approach. The technical procedure used to collect the data was a survey with an additional source from the technical visit to a representative supplier of the automotive industry, aiming to deepen some pertinent questions. The data collection was carried out through questionnaires, semistructured interview, direct observation and documentary analysis. The main objective of the research was to verify the level of formalization of supply logistics of the Brazilian automakers. Therefore, in order to attend this objective, it was necessary to verify the concepts and technological tools used in the activities involved in the supplying processes of the output, aiming at the resources optimization; analyze whether or not the SCM vision of the suppliers converges with the SCM vision of the automakers, and diagnose the existence of partnerships between suppliers and clients. It was verified that, among the factors considered, the difficulty of implementation of the SCM concept is detached as the incoherence in the culture of the companies researched, concerning the partnerships and the information exchanging among the involved members.